Brønsted Acid Catalyzed Asymmetric Silylation of Biaryl Diols - Han, Jung Tae; Zhou, Hui; List, Benjamin (Synlett, 2023)
We report a Brønsted acid catalyzed enantioselective silylation of biaryl diols with an allylsilane as a silicon source. This process enables facile access to enantioenriched biaryl silyl ethers with an axial stereogenicity. A control experiment supports a mechanism proceeding by desymmetrization followed by kinetic resolution.
Keywords: Brønsted acid; imidodiphosphorimidate; silylation; axial chirality; desymmetrization; kinetic resolution